Mukhamandapa (front porch) of the Mahishasuramardini Temple - Temples of India Project Team (Jio Institute, 2024)
The mukhamandapa (front porch) of the Mahishasuramardini Temple, has two pillars at the front and two pilasters at the back. At the top of the shaft, an abacus is placed, carved with divine figures and female attendants. The mukhamandapa leads to the antarala (vestibule), which further leads to the entrance door of the garbhagriha (sanctum sanctorum). The door is carved and depicts Maheshwari, Brahmani, and Vaishnavi on the lintel.